2007
DOI: 10.1016/j.jpowsour.2007.04.078
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of electrochemical characteristics of natural graphite negative electrode coated with polyacrylic acid in pure propylene carbonate electrolyte

Abstract: In order to improve the negative electrode characteristics of a graphite electrode in a propylene carbonate (PC) -containing electrolyte, we have prepared a graphite negative electrode coated with a water-soluble anionic polymer as a binder for composite graphite electrodes. The electrochemical characteristics of the coated graphite were evaluated by cyclic voltammetry and charge-discharge cycle tests. The coated graphite negative electrode showed a stable Li + ion intercalation / deintercalation reaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…The natural graphite (Kansai Coke and Chemical Co. NG-3) electrodes coated with the PAA binder and PVdF binder were prepared in a similar way as previously reported [7]. In…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The natural graphite (Kansai Coke and Chemical Co. NG-3) electrodes coated with the PAA binder and PVdF binder were prepared in a similar way as previously reported [7]. In…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, our group found that polyacrylic acid (PAA), which is a water-soluble polymer, was able to be used as the binder of the graphite electrode [7]. In a propylene carbonate (PC)-based electrolyte, electrochemical Li + ion intercalation into graphite layers does not occur due to the co-intercalation and significantly reductive decomposition of PC molecules at around 1.0 V vs. Li/Li + , causing exfoliation of the graphite layers [8].…”
Section: N N-diethyl-n-methyl-n-(2-methoxyethyl) Ammonium Bis(triflumentioning
confidence: 99%
See 1 more Smart Citation
“…In both these applications, the introduction of graphite increases the electric conductivity of the polymer [13,14], but the addition of inorganic dopants could have an important influence on the microscopic physical properties of the polymeric matrix, modifications that can be investigated only by spectroscopic techniques. The aim of our study was the observation of possible modifications in the local structure of PAA induced by the addition of graphite to the polymeric matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium and sodium salts of carboxymethyl cellulose (NaCMC and LiCMC) and xanthan gum (XG) or the conjugated polymer poly(3,4-ethylenedioxythiophene) (PEDOT) were investigated as binders for MCMB carbon anodes [9]. In order to improve the negative electrode characteristics of a graphite electrode in a propylene carbonate (PC)-containing electrolyte, Koichi et al [10] have prepared an electrode coated with a watersoluble polyacrylic acid (PAA) as a binder. Park et al [11] have investigated the use of PAA as a binder for siliconbased anode finding that the electrode containing the PAA has a lower first-cycle irreversible capacity when compared to the traditional electrodes.…”
Section: Introductionmentioning
confidence: 99%